Spontaneous Rupture of the Urinary Bladder 10 Years after Curative Radiotherapy - Apostolos P. Labanaris; Vahudin Zugor; Reinhold Nützel; Reinhard Kühn (The Scientific World Journal)
It has been reported that the rate of clinically relevant side effects following curative radiotherapy for primary carcinoma is about 3% for urologic complications. Such complications include hematuria, fibrosis, and cystitis. An extremely rare, but dangerous, medical complication following curative radiotherapy that can also be noted is spontaneous bladder perforation. We present such a case of a 27-year-old patient with spontaneous bladder perforation, who was initially misdiagnosed because of its rarity as well as unspecific clinical and laboratory findings.